2017
DOI: 10.1159/000479013
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Induced Nephropathy Is Less Common in Patients with Good Coronary Collateral Circulation

Abstract: Background/Aims: Contrast-induced nephropathy (CIN) is a typically reversible type of acute renal failure that develops after exposure to contrast agents; underlying endothelial dysfunction is thought to be an important risk factor for CIN. Although the mechanism of coronary collateral circulation (CCC) is not fully understood, a pivotal role of the endothelium has been reported in many studies. The aim of this study was to investigate whether there is a relationship between CCC and CIN. Methods: Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In a previous study, we showed that there was a close relationship between CAN and CCC in patients between the ages of 18-75 and coronary collateral development was an independent predictor for CAN [24]. However, in this study, we included patients aged 90 and over; In both binary comparisons and logistic regression analyzes, we found that there was no relationship between these two entities.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study, we showed that there was a close relationship between CAN and CCC in patients between the ages of 18-75 and coronary collateral development was an independent predictor for CAN [24]. However, in this study, we included patients aged 90 and over; In both binary comparisons and logistic regression analyzes, we found that there was no relationship between these two entities.…”
Section: Discussionmentioning
confidence: 63%